THE INFLUENCE OF EMPLOYEE DISCIPLINE ON SERVICE QUALITY AT MAYANG PUBLIC HEALTH CENTER, JEMBER REGENCY - Oktavianingrum, Irma; Hapsari, Yusita Titi; Wardhani, Roro Aditya Novi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The quality of primary healthcare services is largely determined by the behavior of human resources, particularly employee discipline in carrying out tasks. In the context of Mayang Public Health Center, Jember Regency, discipline emerges as a strategic factor, as the high intensity of interactions with patients requires services that are fast, accurate, and professional. This study focuses on analyzing the influence of employee discipline on service quality, based on the assumption that work discipline serves as the foundation influencing ethics, responsiveness, communication, empathy, and professionalism in healthcare services. Methods: A quantitative approach with an ex post facto design was employed. The research population consisted of all 71 employees of Mayang Health Center, with a saturated sample of 71 respondents. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression to examine the relationship between discipline and service quality. Results: The findings reveal that discipline significantly contributes to service quality with a determination value of 65%, while the remaining 35% is influenced by other factors such as motivation, work environment, and competence. The dimensions of discipline, ethics, responsiveness, communication, and professionalism were all rated very high, with discipline making the largest contribution to patient satisfaction. Conclusion and Suggestion: Specialization is confirmed as the primary determinant of healthcare service quality, enriching theoretical models of service quality by positioning discipline as a key variable. Practically, the management of health centers should prioritize discipline as a core performance indicator, while local governments are encouraged to strengthen regulations on human resource discipline in healthcare. Keywords: Discipline, Healthcare Services, Human Resources, Public Health Center, Service Quality